Essentializing Muslims in Ecuadorian Journalism - Troy E. Spier (Lenguaje)
The relationship between Latin America and the so-called ‘Muslim World’ is a tenuous one, as public perceptions of Muslims are generally quite negative despite consistent, typically economically beneficial historical and contemporary immigration from the Middle East. Indeed, despite Muslims constituting less than one-tenth of one percent (0.011%) of the total population in the predominantly Catholic country of Ecuador, which is located in northwestern South America, anti-Muslim sentiments are increasing both in frequency and severity. As a result, this article contextualizes the reality and challenges of Muslims in Ecuador by offering a thematic analysis of almost one-thousand articles concerning Muslims in El Comercio, the Quito-based, leading newspaper of Ecuador. Two subcorpora were created and are referenced here, one containing article titles (3,095 words) and one containing article content (543,389 words). By utilizing a computationally-driven, mixed methods approach to extract and examine these articles, this analysis is couched within the understanding that discourses surrounding Muslims overwhelmingly perpetuate and reinforce negative stereotypes through deliberate rhetorical choices.